Radius of Strong Starlikeness for Some Classes of Analytic Functions - Keerthi, B Srutha; Gangadharan, A; Chinthamani, S (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Let φ(z) be an analytic function with positive real part on ∆ = {z; |z| < 1} with φ(0) = 1, φ 0 (0) > 0 which maps the unit disk ∆ onto a region starlike with respect to 1 and symmetric with respect to the real axis. The radii of strong starlikeness of certain classes of analytic functions are computed.